Analysis of Aspiration Factors becoming Mathematics Teacher that Influence High School Students’ Decision to Choos Mathematics Education Program - Siregar, Rama Nida ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
The importance of the ideal factor in making decisions to choose a program is the urgency of this study. The purpose is to describe the factors of the ideal of becoming a mathematics teacher that influence students in making decisions to choose the mathematics education program at UIN SYAHADA Padangsidimpuan candidates in 10 respondents. The qualitative descriptive is the approach taken in this study. The method of sampling targeted/purposive and snowball data sources, triangulation data collection methods, inductive/qualitative data analysis and qualitative research results emphasize these methods in one method. The results showed that the ideal factor of becoming a mathematics teacher was found in making decisions to choose the mathematics education. After analyzing the information that the researcher collected, it was found based on the results of the analysis questionnaires distributed and interviews with respondents/students who were active in the mathematics education department, several effective factors in the field were found that influenced students to choose the mathematics education section, namely the ideal factor of becoming a mathematics teacher. Based on these results, it shows that one of the factors that influences students to choose a mathematics education program is the aspiration factor to become a mathematics teacher. The aspiration factor to become a mathematics teacher is related to choice of mathematics education program. Of all the problems answered by mathematics education students, there were 10 respondents who in accordance with the aspiration factor to become a mathematics teacher in making decisions about choosing a mathematics education program.